A novel water-based process produces eco-friendly bio-adhesive made from green cross-linked soybean soluble polysaccharide and soy protein. (1st August 2017) - Yuan, Cheng; Chen, Mingsong; Luo, Jing; Li, Xiaona; Gao, Qiang; Li, Jianzhang
Highlights: Developing eco-friendly bio-adhesive from two components in soybean meal. Polysaccharide is crosslinked by a green process to enhance hydrophobicity. Combination of CL-SPSS and SPI formed a stable interpenetrating network structure. Using CL-SSPS creates a smooth and compact cross section of the cured adhesive. Using CL-SSPS improves the water resistance of adhesive by 67.8%. Abstract: In this study, an eco-friendly soy protein adhesive was developed that utilized two components from soybean meal without addition of any toxic material. A plant-based, water-soluble and inexpensive soybean soluble polysaccharide was used as the novel renewable material to combine with soy protein to produce a soy protein adhesive. Three-plywood was fabricated with the resulting adhesive, and its wet shear strength was measured. The results showed the wet shear strength of plywood bonded by the adhesive reached 0.99 MPa, meeting the water resistance requirement for interior use panels. This improvement was attributed to the following reasons: (1) Combination of cross-linked soybean soluble polysaccharide and soy protein formed an interpenetrating network structure, improving the thermal stability and water resistance of the cured adhesive. (2) Adding CL-SSPS decreased the adhesive viscosity to 15.14 Pa s, which increased the amount of the adhesive that penetrate the wood's surface and formed more interlocks.